An investigation of the noise field from a small jet and methods for its reduction. - Westley, R.; Lilley, G. M. (College of Aeronautics, Cranfield, 1952)
Sound measurements have been made on the noise from the jet of a one inch diameter convergent nozzle at atmospheric temperature and at speeds above and below choking. The noise level and spectrum have been investigated in both the near and distant fields. The results agree in some measure with the predictions of the Lighthill theory, that the elementary sound radiator is an acoustic quadrupole. The agreement is more marked if attention is confined to the higher frequencies. Simple empirical formulae are derived giving the overall sound intensity and frequency spectrum in terms of the position relative to the jet, the stagnation pressure excess over the atmospheric pressure, and the frequency. The results of tests on various noise reduction devices are discussed. These tests indicate promising lines of investigation. The maximum reduction in total noise level was about 10 db.